Innovative Financing for Enterprises - Kaliyeva, G.T.; Arystanbaeva, S.S.; Zhanakova, N.N.; Kapenova, A.Z.; Djumabekova, A.T.; Orazbaeva, A.G. (European Research Studies Journal Volume XXI, Issue 2, 307 - 317, 2018)
The industrial and innovative development of Kazakhstan accounts for the growth of the national economy. Although the return on investment in innovative business is quite high in the global financial market in general, individual investors may either get very high profits or lose all their invested funds, which is unacceptable for enterprises. Therefore, it is especially important to define strategic approaches to reduce the potential loss ratio and increase the commercial success of innovation projects. For this purpose, it is necessary to properly and systematically form the financing sources of enterprises’ innovative development, the effectiveness of which is confirmed by international and Kazakh experience. On the other hand, it is important to determine directions and conditions for the use of these funds in the course of the innovation process, since the timely suspension or termination of the project will significantly reduce possible losses
Keywords: Financing sources, innovation, cost of innovation, public financing